Risk factors of hemodialysis catheter dysfunction in patients undergoing continuous renal replacement therapy: a retrospective study - Leerang Lim; Jung Yeon Park; Hannah Lee; Seung-Young Oh; Christine Kang; Ho Geol Ryu (BMC Nephrology, 2023)
Abstract Background Continuous renal replacement therapy is a relatively common modality applied to critically ill patients with renal impairment. To maintain stable continuous renal replacement therapy, sufficient blood flow through the circuit is crucial, but catheter dysfunction reduces the blood flow by inadequate pressures within the circuit. Therefore, exploring and modifying the possible risk factors related to catheter dysfunction can help to provide continuous renal replacement therapy with minimal interruption. Methods Adult patients who received continuous renal replacement therapy at Seoul National University Hospital between January 2019 and December 2021 were retrospectively analyzed. Patients who received continuous renal replacement therapy via a temporary hemodialysis catheter, inserted at the bedside under ultrasound guidance within 12 h of continuous renal replacement therapy initiation were included. Results A total of 507 continuous renal replacement therapy sessions in 457 patients were analyzed. Dialysis catheter dysfunction occurred in 119 sessions (23.5%). Multivariate analysis showed that less prolonged prothrombin time (adjusted OR 0.49, 95% CI, 0.30–0.82, p = 0.007) and activated partial thromboplastin time (adjusted OR 1.01, 95% CI, 1.00–1.01, p = 0.049) were associated with increased risk of catheter dysfunction. Risk factors of re-catheterization included vascular access to the left jugular and femoral vein. Conclusions In critically ill patients undergoing continuous renal replacement therapy, less prolonged prothrombin time was associated with earlier catheter dysfunction. Use of left internal jugular veins and femoral vein were associated with increased risk of re-catheterization compared to the right internal jugular vein.